(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Fusarium species are causing postharvest stem-end rot and dry rot throughout the potato growing season. At the current study, the causative wilt agent was identified in potatoes which were grown in Nineveh province, northern of Iraq, in autumn season of 2020. The disease manifests through symptoms like partial yellowing between the veins on the leaves of potatoes or overall wilting of the plant. Fungal species isolated from the infected potato plants were subsequently grown on potato dextrose agar, resulting in developing aerial mycelia appeared as white along violet-dark pigmentation. The fungus was identified from the phenotypic diagnosis as Fusariumoxysporum, and the pathogen was confirmed by Koch’s hypotheses as well as affirmed through molecular test identification, where methodology proved it. Molecular based pathogen identification was carried out through an application of conserved DNA ribosomal region of internal transcribed spacer (ITS). Moreover, the complete verified ITS sequences are homologous to theisolates of Fusariumoxysporum in GenBank database having 99% similarity. At Gen-Bank, isolated one in Iraq was given #: MH859948.1 being an Accession. The best to the available knowledge, such is Fusariumoxysporum f. sp. tuberosi 1st molecular Potato record in Iraq